2014
DOI: 10.11118/actaun201462050849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Compost Doses on the Soil Infiltration Capacity

Abstract: . It was found out within the study period that the application of the higher compost doses showed a positive eff ect on infi ltration rate in both localities. In Variant 3, the highest values of the water infi ltration were recorded. It can be concluded that the highest dose of compost (150 t.ha −1 ) improved and accelerated both the infi ltration and water holding capacity of soil for a longer period. With the exception of the year 2009, increased values of water infi ltration were recorded on experimental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Tey found that the runof and water erosion on sandy soil were signifcantly reduced by the compost application. Badalíková and Bartlová [51] found out within the study period that the application of the higher compost doses showed a positive efect on infltration rate in loamy sand and sandy loam soils. Schmid et al [52] also reported that the addition of compost resulted in an increase in water content compared to the control.…”
Section: Discussionmentioning
confidence: 94%
“…Tey found that the runof and water erosion on sandy soil were signifcantly reduced by the compost application. Badalíková and Bartlová [51] found out within the study period that the application of the higher compost doses showed a positive efect on infltration rate in loamy sand and sandy loam soils. Schmid et al [52] also reported that the addition of compost resulted in an increase in water content compared to the control.…”
Section: Discussionmentioning
confidence: 94%